The hidden pain of surgical scars: exploring scar endometriosis - N., Sunanda; D., Poornima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Scar endometriosis is a rare disease and is difficult to diagnose. The symptoms are nonspecific, typically involving pain at the incision site at the time of menstruation. It commonly follows obstetrical and gynaecological surgeries. The diagnosis is frequently made only after excision of the diseases tissue. The case reports of the patients with a troublesome scar after a caesarean section are presented. Surgical excision led to the diagnosis of scar endometriosis. The Pathogenesis, diagnosis and treatment of this somewhat rare condition are discussed.